A guide to the fishers of Queensland - Fenton, D. Mark (CRC Reef Research technical report ;, 2001)
This report describes the social and financial characteristics of the ... fishing industry in in Queensland. It also identifies the social and financial relationships between the fisheries resource and coastal communities within a research framework known as TRC Analysis.